Gastroenterologists attitude in various clinical settings in the era of COVID-19 pandemic: An online Uni-National Israeli Survey. Issue 30 (30th July 2021) - Sbeit, Wisam; Mari, Amir; Khoury, Tawfik
Abstract : Abstract: Coronavirus disease 2019 (COVID-19) pandemic has impacted our clinical practice. Many gastroenterologists have changed their attitudes toward various gastroenterological clinical settings. The aim of the present study is to explore the gastroenterologist's attitudes in several clinical settings encountered in the clinical practice. An online based survey was completed by 101 of 250 Israeli gastroenterologists (40.5%). Most of the participants were males (76.2%), and most of them were in the age range of 40 to 50 (37.6%). For all questionnaire components, the 2 most common chosen options were "I perform endoscopy with N95 mask, gloves and gown protection in a standard endoscopy room without preendoscopy severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) testing" and "Tend to postpone endoscopy until SARS-CoV-2 test is performed because of fear from being infected, or virus spreading in the endoscopy suite." Notably, 12 (11.9%) gastroenterologists were infected by Coronavirus disease 2019 during their work. Classifying the clinical settings to either elective and non-elective, most gastroenterologists (77.4%) chose the attitude of "I perform endoscopy with N95 mask, gloves and gown protection in a standard endoscopy room without SARS-COV-2 testing" in the nonelective settings as compared to 54.2% for the elective settings, ( P < .00001), whereas 32.9% of the responders chose the attitude of "Tend to postpone endoscopy until SARS-COV-2 test is performed because of fear from being infected, or virus spreading in the endoscopy suite" in the elective settings ( P < .00001). Gastroenterologists' attitude in various gastroenterological settings was based on the clinical indication. Further studies are needed to assess the long-term consequences of the different attitudes. Abstract : Supplemental Digital Content is available in the text